2004
DOI: 10.1007/s00464-003-9001-4
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic cholecystectomy in patients with previous upper or lower abdominal surgery

Abstract: Previous abdominal operations, even in the upper abdomen, are not a contraindication to safe laparoscopic cholecystectomy. However, previous upper abdominal surgery is associated with an increased need for adhesiolysis, a higher open conversion rate, a prolonged operating time, an increased incidence of postoperative wound infection, and a longer postoperative stay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
41
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(44 citation statements)
references
References 15 publications
2
41
1
Order By: Relevance
“…This is similar to the results of Karayiannakis et al [23] who reported a higher conversion rate in patients who had undergone upper abdominal operations (19 vs. 5%). In our opinion, a history of upper abdominal operation should not be considered a contraindication to LC.…”
Section: Discussionsupporting
confidence: 82%
“…This is similar to the results of Karayiannakis et al [23] who reported a higher conversion rate in patients who had undergone upper abdominal operations (19 vs. 5%). In our opinion, a history of upper abdominal operation should not be considered a contraindication to LC.…”
Section: Discussionsupporting
confidence: 82%
“…To expand the indications, the safety of the procedure as well as the oncologic aspects need to be assessed. Two earlier studies on the impact of previous abdominal surgery showed little influence on the short-term outcome after laparoscopic and open procedures, but included a relatively small number of patients [12,14]. Compared with those reports, our series included a larger number of patients, so the findings are probably more reliable.…”
Section: Discussioncontrasting
confidence: 41%
“…There have been few reports about the impact of previous abdominal surgery on laparoscopic procedures including colorectal surgery [11,12,13], but this issue should be studied further in order to expand the indications of laparoscopic surgery and benefit to patients. To expand the indications, the safety of the procedure as well as the oncologic aspects need to be assessed.…”
Section: Discussionmentioning
confidence: 99%
“…7,26,27 Finally, prior abdominal surgery has also been associated with a higher likelihood of conversion in numerous studies. 7,8,28 Prior surgery, especially in the upper abdomen, may result in adhesions around the gallbladder, limiting visualization, retraction, and dissection. 28 Adhesions were the most commonly cited reason for conversion in the present study, and almost half of the patients undergoing conversion had a history of abdominal surgery.…”
Section: Discussionmentioning
confidence: 99%
“…7,8,28 Prior surgery, especially in the upper abdomen, may result in adhesions around the gallbladder, limiting visualization, retraction, and dissection. 28 Adhesions were the most commonly cited reason for conversion in the present study, and almost half of the patients undergoing conversion had a history of abdominal surgery. While the aforementioned patient factors certainly contribute to unsuccessful LCs, it is generally accepted that the most important factors are surgeon-specific.…”
Section: Discussionmentioning
confidence: 99%